Taxonomy, systematics and DNA barcoding of selected Penicillium groups - Rivera, Karol Geraldina (University of Ottawa (Canada), 2009)
Cytochrome c oxidase subunit 1 (Cox 1) is the barcode for many animal groups, protists, and macroalgae. Previously in fungi, the efficiency of Cox 1 as a genetic marker was only analysed in Penicillium subgenus Penicillium and Leohumicola spp. In this thesis, two species isolated from the intestinal tracts of caterpillars from Costa Rica, and two potential species complexes, P. sclerotiorum and P. oxalicum belonging to Penicillium subgenus Aspergilloides and Furcatum, were studied using the Genealogical Concordance Concept (Gee) recognition criterion and barcoding methods. Analyses with beta-tubulin (BenA), the nuclear internal transcriber spacer (ITS) region, Cox 1, translation elongation factor 1-alpha (TEF1-alpha), and calmodulin (CaM) revealed that the Penicillium species isolated from Costa Rica are undescribed, and that P. sclerotiorum is a complex of seven phylogenetic species (including the Costa Rican species) that fit the prevailing morphological concept of P. sclerotiorum. The phylogenetic species were compared and newly discovered diagnostic morphological characters were used to create a taxonomic key to the species of the complex. The new species are formally described as P. guanacastense, P. mallochii, P. krugii, P. cainii, P. jacksonii and P. ciebiessum. Analyses of multiple strains of P. oxalicum revealed that it is a single phylogenetic species, despite having a world wide distribution, an unusually high degree of morphological variation, and a diversity of ecological roles. Cox1 proved to be a good barcode for identifying the selected Penicillium groups, and provided a species level resolution of 83.3%. ITS provided the same resolving ability. BenA (91.7%), TEF1-alpha (100%) and CaM (100%) provided a higher species level resolution than Cox1, but BenA, TEF1-alpha, and CaM were difficult to amplify or sequence for some Penicillium groups. A secondary barcode marker is suggested in addition to Cox1 for Penicillium.
Keywords: Biology, Systematic.